2003
DOI: 10.1242/jcs.00428
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 phosphorylation at S368 is acute during S and G2/M and in response to protein kinase C activation

Abstract: Phorbol esters such as 12-O-tetradeconylphorbol-13-acetate (TPA)activate protein kinase C, increase Connexin43 (Cx43) phosphorylation, and decrease cell-cell communication via gap junctions in many cell types. Previous work has implicated protein kinase C (PKC) in the direct phosphorylation of Cx43 at S368, which results in a change in single channel behavior that contributes to a decrease in intercellular communication. We have examined Cx43 phosphorylation in several cell lines with an antibody specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
125
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 40 publications
13
125
0
1
Order By: Relevance
“…To look at this further, we examined the ability of Cx43 mutated at these sites to shift in response to stimuli, both experimentally and in the literature. We have shown previously that HeLa cells expressing wild type Cx43 or Cx43 with a S368A mutation exhibit a migration shift in response to PMA (Solan et al, 2003). Here, we show that in HeLa cells expressing a S262A mutant, Cx43 does not shift to the P2 form in response to PMA treatment, although we did observe an apparent shift to a position just above the P0 form (Fig.…”
Section: Phosphorylation On S262 Creates a Distinct P2 Isoform Of Cx43supporting
confidence: 52%
See 1 more Smart Citation
“…To look at this further, we examined the ability of Cx43 mutated at these sites to shift in response to stimuli, both experimentally and in the literature. We have shown previously that HeLa cells expressing wild type Cx43 or Cx43 with a S368A mutation exhibit a migration shift in response to PMA (Solan et al, 2003). Here, we show that in HeLa cells expressing a S262A mutant, Cx43 does not shift to the P2 form in response to PMA treatment, although we did observe an apparent shift to a position just above the P0 form (Fig.…”
Section: Phosphorylation On S262 Creates a Distinct P2 Isoform Of Cx43supporting
confidence: 52%
“…Activation of specific kinases changes the gating properties of gap junction channels, the extent of gap junction assembly, the half-life of Cx43 and, in some cases/cell types, its electrophoretic mobility. Previously we showed that activation of protein kinase C led to phosphorylation of Cx43 at S368 (Lampe et al, 2000) with a change in electrophoretic mobility in Chinese Hamster Ovary (CHO) but not Normal Rat Kidney (NRK) cells (Solan et al, 2003). Here, we show that the change in electrophoretic mobility was apparently due to different pools of Cx43 being phosphorylated on S262 via MAPK activation.…”
Section: Introductionmentioning
confidence: 61%
“…The looser interactions with residues Ser-364 -Ala-371 may play a more regulatory role with other Cx43 molecular partners. It is perhaps noteworthy that this region contains three phosphorylatable residues: protein kinase C phosphorylates Cx43 on Ser-368 and Ser-372 (7,63), leading to decreased junctional conductance (64 -66), whereas phosphorylation of Ser-364 by cAMP-dependent protein kinase increases gap junctional communication (67,68). Whether phosphorylation of this region alters binding affinity to intracellular ligands remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Since such CDK-inhibitors block the cell cycle and are invovled in stimulating apoptosis, the previous findings established a link between gap junction coupling and regulation of cell cycle and apoptosis as it was recently proposed [10]. Similarly, a PKC-dependent phosphorylation of Cx43 that correlates with a reduction of gap junction coupling was found during G2/M phase of the cell cycle [11] GFSHR-17 granulosa cells, the in vitro model for granulosa cells of the maturing ovular follicle, are a suitable cell system for the analysis of gap junction coupling and apoptosis [12]. They form gap junction channels mainly formed by Cx43 and Cx45 [13], which regulate follicular development and atresia [14][15][16].…”
Section: Introductionmentioning
confidence: 84%